GAYA KELEKATAN DAN KEMARAHAN - Penny Cahyani; Asmadi Alsa; Avin Fadilla Helmi (Jurnal Psikologi, 1999)
This study was purposed to differencences angry (experience angry and expression anger) on attachment style (secure, with drawl, and anxious). The hypothesis was that there were differences angry scores (experience angry and expression angry) on attachment styles (secure withdrawal, and anxious). Subject with secure attachment was angry score higher than subject with withdrawal and anxious attachment style. There was 100 subjects participation in this study. There were two scales, which are attachment style scale and State-Trait Anger Expression Inventory (STAXY). The result is that there is differences experience and expression anger between three attachment styles. Subject with secure attachment style have experiences angry (trait anger & state anger) and expressions anger (anger-in, anger-out) lower than subjects with the others; and mean score anger control subject’s is higher than the others. Keywords: attachment style, angry